THE ERGODICITY OF THE OBSERVED PROCESS OF A HIDDEN MARKOV MODEL - SETIAWATY, B. (School of Data Science, Mathematics and Informatics, IPB University, 2004)
This paper presents some properties of a stationary hidden Markov model. The most important is the ergodicity of the observed process which is essential for limit theorems.